Landscape organization of monumental sculpture in the creative work of Arnold Röhring (squares, streets and parks of the city) - Posatskyy, Bohdan; Hrytsak, Mykhailo (Видавництво Львівської політехніки, 2016)
The article deals with the landscape arrangement of monumental sculptures in the creative work of Arnold Röhring. The text reviews the role and the importance of landscape arrangement of monumental sculptures in the architectural composition of the city of Lviv. Examples of works of monumental sculpture of the turn of the 19th and 20th centuries are described in the article. Статтю присвячено аналізу ландшафтного оточення монументальної скульптури у творчості Арнольда Рерінга. Розглянуто роль і значення ландшафтної організації монументальної скульптури у архітектурній композиції Львова. Наведено приклади організації творів монументальної скульптури на зламі ХІХ–ХХ ст.
Ландшафтна організація творів монументальної скульптури у творчості Рерінга (на площах, вулицях та у парках Львова)
Keywords: monumental sculpture; Arnold Röhring; landscape organization; city parks; монументальна скульптура; Арнольд Рерінг; ландшафтна організація; парки Львова